(untitled) (World Bulletin of Education and Learning, 2025)
This article provides information about the period of ancient Inner Asia from the 3rd-2nd centuries BC to the 6th-7th centuries AD, about the nomads who lived in the region, their lifestyle, and their economy. In addition, it provides information about the wars between the nomadic Huns and the nomadic Yuezhi and their relations with the Han dynasty in ancient China. It provides news about the specific aspects of the migration of nomads across the region, such as moving from north to south, southwest, that is, to the territories of our region.